A method for preparing modified flax yarn capable of reducing flax yarn breakage
Through a multi-step soaking treatment process, composite enzyme solution and other solutions are used to remove impurities, swell fibers, and improve functional group structure, which solves the problems of poor tensile performance of linen yarns and the difficulty of waste liquid treatment, and achieves efficient modification of linen yarns and environmentally friendly craftsmanship.
Patent Information
- Application Number
- CN202211474736.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-23
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-11-23
AI Technical Summary
In the prior art, the tensile resistance of linen yarns is poor, and the waste liquid is difficult and costly in the modification treatment process, resulting in environmental pollution and waste of resources.
Using a multi-step soaking process of composite enzyme solution, NH3-urea solution, ammonium bicarbonate solution, potassium permanganate solution and glycerol solution, the flax fiber is improved by removing impurities, swelling fibers, improving functional group structure and regulating surface performance. tensile resistance and fracture resistance.
It significantly improves the tensile breaking strength and tensile elongation of the linen yarn fiber, reduces the breaking rate of the linen yarn, simplifies the process flow, reduces the treatment cost, and is easy to treat waste liquid, and reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textile materials, in particular to a method for preparing modified flax yarn capable of reducing flax yarn breakage. Background Art
[0002] Linen yarn fabrics have the characteristics of fast moisture absorption and moisture dissipation, breathable and smooth, and natural texture, and are favored by consumers at home and abroad. Linen yarn is made of linen fiber. Therefore, the quality of linen fiber will directly affect the quality of linen yarn. For example, the tensile strength of linen fiber will directly affect the breakage rate of the prepared linen yarn. However, linen fiber has a high impurity content and poor spinning performance. The cleanliness and orientation of linen fiber are high, resulting in poor inward penetration and diffusion of dyes, and easy to break and poor tensile strength.
[0003] Based on this, some researchers have carried out research on the modification of flax fibers. For example, patent No. 201611106252.8 discloses a technical solution for the modification of flax staple fibers, which is pre-treated by the waste alkali circulation and re-boiling method, and then processed by sodium periodate for selective oxidation, glycerol solution immersion, deionized water washing, dehydration, and drying. Among them, the waste alkali circulation liquid treatment is: sodium carbonate 6g / L, sodium sulfite 3g / L, urea 8g / L, temperature 90-95℃, time 50-60min, bath ratio 1: 30, cycle scouring; washing with warm water, sodium periodate at a concentration of 4-5g / L, temperature of 35-45°C, time of 30-40min, bath ratio of 1:30, immersion oxidation treatment in dark, then immersion in glycerol solution, washing with deionized water, so that the aldehyde content of the modified flax staple fiber is 216.67-233.58mmol / g, o'KI infrared crystallization index is 0.8285-0.8374, splitting degree is 1225-1262Nm, and breaking strength is 7.64-8.40cN·tex -1 , elongation 4.97-5.46%, whiteness 72.11-75.03%, in order to improve the comprehensive performance of flax fiber. However, the method needs to strictly limit the concentration, temperature and time of sodium periodate, otherwise the sodium periodate will deepen the oxidation degree of flax fiber, the degree of degradation and weight loss rate will be too large, and then the comprehensive performance of flax fiber after modification will deteriorate; at the same time, the method also introduces strong alkaline components such as sodium sulfite and sodium carbonate for soaking and boiling, so that the waste liquid after treatment is recycled and discharged, which will cause serious environmental pollution and is difficult to recycle.
[0004] Another example: Patent No. 201811067891.7 discloses a method for improving the mechanical properties of linen yarn, using cellulase treatment, modification treatment and 12 C 6+Ion beam irradiation treatment, specifically, using cellulase solution to treat the linen yarn for 12-15 minutes, taking out and soaking the linen yarn in anhydrous ethanol for 40-50 seconds, and drying it naturally to constant weight; then using deionized water and linen yarn in a mass ratio of 10-12:1 to prepare a linen yarn dispersion, then adding an initiator ammonium sulfate solution and stirring evenly, then adding N-hydroxyethyl acrylamide solution, water bathing at 75°C for 1.5 hours, keeping warm for 1 hour to obtain a mixed dispersion, adjusting the pH to 8.0 with a sodium hydroxide solution with a concentration of 1.2 mol / L, ultrasonically treating for 10 minutes, filtering, obtaining modified linen yarn, and after natural drying, irradiating, washing with anhydrous ethanol and deionized water for 5 minutes each, and vacuum drying to constant weight to obtain; improving the tensile performance so that the breaking strength reaches 61.05 cN·tex -1 However, the tensile properties of the linen yarn formed by this method are still poor, the elongation at break is still low, and the treatment process requires the use of strong alkaline components such as sodium hydroxide to adjust the pH, which makes the treatment of the filtered liquid difficult and the waste liquid treatment cost high.
[0005] In view of this, the researchers based themselves on their long-term research practice and theoretical basis on flax yarn fibers, with the goal of reducing the breakage rate of flax yarn and improving the tensile properties of flax yarn. At the same time, they reduced the difficulty of waste liquid treatment in the flax yarn modification process and reduced the treatment cost, providing a new idea for the field of flax yarn modification. Summary of the invention
[0006] In order to solve the above technical problems existing in the prior art, the present invention provides a method for preparing modified flax yarn which can reduce the breakage of flax yarn.
[0007] This is achieved specifically through the following technical solutions:
[0008] A method for preparing modified flax yarn capable of reducing flax yarn breakage comprises the following steps:
[0009] (1) soaking the flax yarn in a composite enzyme solution for 10-15 minutes, then taking it out and drying it in a natural environment to constant weight, then treating it with NH3-urea solution for 5-15 minutes, and then taking it out and drying it to constant weight to obtain crude fiber;
[0010] (2) soaking the crude product in an ammonium bicarbonate solution for at least 30 minutes, then taking it out and soaking it in a potassium permanganate solution in the dark for 30 minutes, taking it out, washing it thoroughly with deionized water, dehydrating it, and drying it to a constant weight to obtain a semi-finished fiber;
[0011] (3) soaking the semi-finished product in a propylene glycol solution for 15-20 minutes, then washing it with deionized water, dehydrating it, and drying it to a constant weight to obtain a finished fiber;
[0012] (4) The finished fiber is spun into linen yarn to obtain the composite enzyme solution, which is a solution formed by mixing pectinase and ligninase in a mass ratio of 1:0.3-1, adding 5-10L of water to 1g of the mixed enzyme, and adjusting the temperature to 60-80°C.
[0013] The flax yarn is soaked in a composite enzyme solution composed of pectinase and ligninase to remove a large amount of impurities in the flax yarn, and then soaked in NH3-urea solution to fully swell the fiber and improve the soaking treatment effect; then soaked in ammonium bicarbonate solution and potassium permanganate solution to improve the functional group structure on the flax yarn fiber, and soaked in propylene glycol solution to adjust the surface properties of the flax yarn fiber, thereby improving the overall performance of the flax yarn fiber, so that the tensile strength of the obtained flax yarn fiber is greatly improved, the anti-fracture ability is enhanced, and then the flax yarn breakage rate is reduced.
[0014] In order to improve the swelling effect of linen yarn fiber, ensure the modification effect of linen yarn fiber, and improve the tensile strength of linen yarn fiber, preferably, the NH3-urea solution is prepared by mixing urea and deionized water in a mass ratio of 1:3-5 to form a solution, then introducing ammonia gas or adding ammonium ion components into the solution, adjusting the ammonium ion content in the solution to 5-10 g / L, and adjusting the temperature to 5-10° C. to obtain a mixed solution. More preferably, the ammonium bicarbonate solution immersion is carried out by using an ammonium bicarbonate solution with a concentration of 15-20 g / L and immersing at a constant temperature of 40° C.
[0015] In order to avoid excessive oxidation and degradation of the linen yarn fibers and ensure the comprehensive performance of the linen yarn fibers, preferably, the concentration of the potassium permanganate solution is 6-10 g / L and the temperature is 40-50°C.
[0016] In order to enhance the comprehensive performance of linen yarn fiber and improve the tensile flexibility of linen yarn fiber, preferably, the concentration of the glycerol solution is 3-5g / L and the temperature is 10-15°C. More preferably, preferably, ethylene glycol accounting for 1-7% of the mass of glycerol is added to the glycerol solution. More preferably, the ethylene glycol accounts for 2.6-3.7% of the mass of the glycerol. More preferably, the ethylene glycol accounts for 3.2% of the mass of the glycerol.
[0017] The soaking described in the invention is mixed according to a water bath ratio of 1:25-30.
[0018] Compared with the prior art, the technical effects created by the present invention are embodied in:
[0019] By introducing a composite enzyme solution to soak the linen yarn, impurities on the surface of the linen yarn are degraded and removed, and the linen yarn is soaked in NH3-urea solution to enhance the swelling effect of the linen yarn fiber. After being soaked and absorbed in ammonium bicarbonate solution to form buffering properties, it is soaked in potassium permanganate solution to achieve oxidation and decolorization treatment, thereby improving the linen yarn's resistance to tensile break and enhancing its whiteness. Combined with the immersion treatment in propylene glycol solution, the linen yarn's flexibility is enhanced, its tensile ductility is improved, and its elongation at break is improved.
[0020] The treatment process created by the present invention is simple, the raw material components used are easily available, the cost of modifying the flax yarn fiber is low, the process conditions are simple to control, and it is easy to promote and implement industrialization; at the same time, the alkalinity of the generated waste liquid is relatively weak, which makes it easier to treat and discharge the waste liquid, thus avoiding the defect of high waste liquid treatment cost caused by the flax yarn modification process. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is further defined below in conjunction with specific implementation methods, but the scope of protection required is not limited to the description.
[0022] In certain embodiments, a method for preparing a modified flax yarn that can reduce flax yarn breakage comprises the following steps:
[0023] (1) soaking the flax yarn in a composite enzyme solution for 10-15 minutes, for example: 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, etc., then taking it out and drying it in a natural environment to constant weight, then treating it with NH3-urea solution for 5-15 minutes, for example: 5 minutes, 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes, 15 minutes, etc., then taking it out and drying it to constant weight to obtain crude fiber;
[0024] (2) soaking the crude product in an ammonium bicarbonate solution for at least 30 minutes, for example, 30 minutes, 35 minutes, 40 minutes, etc., then taking it out and soaking it in a potassium permanganate solution in the dark for 30 minutes, taking it out, washing it thoroughly with deionized water, dehydrating it, and drying it to a constant weight to obtain a semi-finished fiber;
[0025] (3) soaking the semi-finished product in a propylene glycol solution for 15-20 minutes, for example, 15 minutes, 16 minutes, 17 minutes, 18 minutes, 19 minutes, 20 minutes, etc., and then washing with deionized water, dehydrating, and drying to constant weight to obtain finished fiber;
[0026] (4) The finished fiber is spun into linen yarn to obtain the composite enzyme solution. The composite enzyme solution is a mixture of pectinase and ligninase in a mass ratio of 1:0.3-1, for example, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, etc., and then 1g of the mixed enzyme is added with 5-10L of water, for example, 1g of the mixed enzyme is added with 5L of water, 1g of the mixed enzyme is added with 6L of water, 1g of the mixed enzyme is added with 7L of water, 1g of the mixed enzyme is added with 8L of water, 1g of the mixed enzyme is added with 9L of water, 1g of the mixed enzyme is added with 10L of water, and the temperature is adjusted to 60-80°C, for example, 60°C, 70°C, 80°C, etc. to form a solution.
[0027] By strictly controlling the process conditions and process steps of immersion treatment with complex enzyme solution, NH3-urea solution, ammonium bicarbonate solution, potassium permanganate solution, and propylene glycol solution, the linen yarn is subjected to the process steps of impurity removal-swelling-buffering-oxidative decolorization-toughening, etc., which improves the overall tensile strength and elongation of the linen yarn fiber, ensures the overall excellent performance of the linen yarn fiber, and does not need to introduce strong alkaline components such as sodium hydroxide, thereby reducing the difficulty of subsequent waste liquid treatment, reducing the cost of waste liquid post-treatment and discharge, and reducing the cost of linen yarn modification.
[0028] In some embodiments, the NH3-urea solution is prepared by mixing urea and deionized water in a mass ratio of 1:3-5, for example, 1:3, 1:4, 1:5, etc., and then introducing ammonia gas into the solution or adding ammonium ion components to adjust the ammonium ion content in the solution to 5-10 g / L, for example, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, etc., to ensure that the solution containing the urea component contains alkaline ammonium ions, promote the action of urea on the linen yarn and enhance the swelling effect of the linen yarn fiber, and adjust the temperature to 5-10°C, for example, 5°C, 6°C, 7°C, 8°C, 9°C, 10°C, etc. to obtain a mixed solution, so that at this temperature, the escape of ammonium ions is suppressed and the swelling effect of the linen yarn fiber is ensured.
[0029] In some embodiments, the ammonium bicarbonate solution immersion is performed using an ammonium bicarbonate solution with a concentration of 15-20 g / L, for example: 15 g / L, 16 g / L, 17 g / L, 18 g / L, 19 g / L, 20 g / L, etc., and the immersion is carried out at a constant temperature of 40°C.
[0030] In some embodiments, the concentration of the potassium permanganate solution is 6-10 g / L, for example: 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, etc., and the temperature is 40-50° C., for example: 40° C., 42° C., 43° C., 46° C., 49° C., 50° C., etc., to ensure the surface effect of the oxidized flax yarn.
[0031] In some embodiments, the concentration of the glycerol solution is 3-5 g / L, for example: 3 g / L, 4 g / L, 5 g / L, etc., and the temperature is 10-15°C, for example: 10°C, 11°C, 12°C, 13°C, 14°C, 15°C, etc. In this way, the flexibility of the flax yarn fiber after oxidation treatment is combined to enhance the tensile strength of the flax yarn fiber and improve the tensile ductility.
[0032] In some embodiments, 1-7% of the mass of glycerol, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, etc., of ethylene glycol is added to the glycerol solution. This ensures that the toughening effect on the linen yarn fiber is enhanced. In a more excellent embodiment, the ethylene glycol accounts for 2.6-3.7% of the mass of the glycerol, such as 2.1%, 2.6%, 2.9%, 3.2%, 3.3%, 3.5%, 3.7%, etc. This can help improve the elongation at break of the linen yarn fiber.
[0033] During the research process, the researchers of the present invention conducted corresponding experimental research on the effects of different process modification treatments on flax yarn fibers, and tested the tensile elongation and tensile strength of the modified flax yarn fibers. The specific operation process is described as follows.
[0034] Example 1
[0035] Pectinase and ligninase were mixed in a mass ratio of 1:0.3, and then 1g of the mixed enzyme was added with 5L of water, and the temperature was adjusted to 60°C to form a composite enzyme solution to soak the linen yarn for 10 minutes, and the water bath ratio for soaking was 1:25. The linen yarn was taken out and dried to constant weight in a natural environment. Urea and deionized water were mixed and dissolved in a mass ratio of 1:3 to form a solution, and ammonia was introduced into the solution. After adjusting the ammonium ion content in the solution to 5g / L, the temperature was adjusted to 5°C to obtain NH3-urea solution, and the linen yarn treated with the composite enzyme solution was placed in the NH3-urea solution at a water bath ratio of 1:25 for 5 minutes, and then taken out and dried to constant weight to obtain crude fiber. The crude fiber was immersed in an ammonium bicarbonate solution with a concentration of 15 g / L and a water bath ratio of 1:25 at a constant temperature of 40°C for 30 minutes, then taken out and placed in a potassium permanganate solution with a concentration of 6 g / L and a temperature of 40°C, immersed in a light-proof water bath ratio of 1:25 for 30 minutes, taken out, fully washed with deionized water, dehydrated, and dried to constant weight to obtain semi-finished fiber; then immersed in a propylene glycol solution with a concentration of 3 g / L and a temperature of 10°C at a water bath ratio of 1:25 for 15 minutes, then fully washed with deionized water, dehydrated, and dried in a vacuum environment at 80°C to constant weight to obtain finished fiber.
[0036] Example 2
[0037] Pectinase and ligninase were mixed in a mass ratio of 1:1, and 10L of water was added to 1g of the mixed enzyme, and the temperature was adjusted to 80°C to form a composite enzyme solution to soak the linen yarn for 15 minutes, and the water bath ratio for soaking was 1:25. The linen yarn was taken out and dried to constant weight in a natural environment. Urea and deionized water were mixed and dissolved in a mass ratio of 1:5 to form a solution, and ammonia was introduced into the solution. After the ammonium ion content in the solution was adjusted to 10g / L, the temperature was adjusted to 10°C to obtain NH3-urea solution, and the linen yarn treated with the composite enzyme solution was placed in the NH3-urea solution at a water bath ratio of 1:25 for immersion treatment for 15 minutes, and then taken out and dried to constant weight to obtain crude fiber. The crude fiber was immersed in an ammonium bicarbonate solution with a concentration of 20 g / L at a constant temperature of 40°C and a water bath ratio of 1:25 for 30 minutes, then taken out and placed in a potassium permanganate solution with a concentration of 10 g / L and a temperature of 50°C, immersed in a light-proof water bath ratio of 1:25 for 30 minutes, taken out, fully washed with deionized water, dehydrated, and dried to constant weight to obtain semi-finished fiber; then immersed in a propylene glycol solution with a concentration of 5 g / L and a temperature of 15°C at a water bath ratio of 1:25 for 20 minutes, then fully washed with deionized water, dehydrated, and dried in a vacuum environment at 90°C to constant weight to obtain finished fiber.
[0038] Example 3
[0039] Pectinase and ligninase were mixed in a mass ratio of 1:0.7, and then 8L of water was added to 1g of the mixed enzyme, and the temperature was adjusted to 70°C to form a composite enzyme solution to soak the linen yarn for 13 minutes, and the bath ratio of the soaking water was 1:25. The linen yarn was taken out and dried to constant weight in a natural environment; urea and deionized water were mixed and dissolved in a mass ratio of 1:4 to form a solution, and ammonia was introduced into the solution. After the ammonium ion content in the solution was adjusted to 6g / L, the temperature was adjusted to 9°C to obtain NH3-urea solution, and the linen yarn treated with the composite enzyme solution was placed in the NH3-urea solution at a bath ratio of 1:28 for immersion treatment for 11 minutes, and then taken out and dried to constant weight to obtain crude fiber. The crude fiber was immersed in an ammonium bicarbonate solution with a concentration of 19 g / L at a constant temperature of 40°C and a water bath ratio of 1:30 for 30 minutes, then taken out and placed in a potassium permanganate solution with a concentration of 7 g / L and a temperature of 43°C, immersed in a light-proof water bath ratio of 1:29 for 30 minutes, taken out, fully washed with deionized water, dehydrated, and dried to constant weight to obtain semi-finished fiber; then immersed in a propylene glycol solution with a concentration of 4 g / L and a temperature of 14°C at a water bath ratio of 1:26 for 16 minutes, then fully washed with deionized water, dehydrated, and dried in a vacuum environment at 75°C to constant weight to obtain finished fiber.
[0040] Example 4
[0041] Pectinase and ligninase were mixed in a mass ratio of 1:0.3, and then 10L of water was added to 1g of the mixed enzyme, and the temperature was adjusted to 70°C to form a composite enzyme solution to soak the linen yarn for 10 minutes, and the water bath ratio for soaking was 1:26. The linen yarn was taken out and dried to constant weight in a natural environment; urea and deionized water were mixed and dissolved in a mass ratio of 1:5 to form a solution, and ammonia was introduced into the solution. After the ammonium ion content in the solution was adjusted to 5g / L, the temperature was adjusted to 5°C to obtain NH3-urea solution, and the linen yarn treated with the composite enzyme solution was placed in the NH3-urea solution at a water bath ratio of 1:28 for immersion treatment for 10 minutes, and then taken out and dried to constant weight to obtain crude fiber. The crude fiber was immersed in an ammonium bicarbonate solution with a concentration of 20 g / L at a constant temperature of 40°C and a water bath ratio of 1:30 for 30 minutes, then taken out and placed in a potassium permanganate solution with a concentration of 7 g / L and a temperature of 40°C, immersed in a light-proof water bath ratio of 1:28 for 30 minutes, taken out, fully washed with deionized water, dehydrated, and dried to constant weight to obtain semi-finished fiber; then immersed in a propylene glycol solution with a concentration of 5 g / L and a temperature of 10°C at a water bath ratio of 1:30 for 20 minutes, then fully washed with deionized water, dehydrated, and dried in a vacuum environment at 100°C to constant weight to obtain finished fiber.
[0042] Example 5
[0043] Pectinase and ligninase were mixed in a mass ratio of 1:1, and 1g of the mixed enzyme was added with 5L of water. The temperature was adjusted to 60°C to form a composite enzyme solution to soak the flax yarn for 10min, and the bath ratio of the immersion water was 1:30. The flax yarn was taken out and dried to constant weight in a natural environment. Urea and deionized water were mixed and dissolved in a mass ratio of 1:5 to form a solution, and ammonia was introduced into the solution. After the ammonium ion content in the solution was adjusted to 10g / L, the temperature was adjusted to 5°C to obtain NH3-urea solution. The flax yarn treated with the composite enzyme solution was placed in the NH3-urea solution at a bath ratio of 1:25 for immersion treatment for 10min, and then taken out and dried to constant weight to obtain crude fiber. The crude fiber was immersed in an ammonium bicarbonate solution with a concentration of 15 g / L at a constant temperature of 40°C and a water bath ratio of 1:30 for 30 minutes, then taken out and placed in a potassium permanganate solution with a concentration of 9 g / L and a temperature of 50°C, immersed in a light-proof water bath ratio of 1:25 for 30 minutes, taken out, fully washed with deionized water, dehydrated, and dried to constant weight to obtain semi-finished fiber; then immersed in a propylene glycol solution with a concentration of 4 g / L and a temperature of 10°C at a water bath ratio of 1:30 for 15 minutes, then fully washed with deionized water, dehydrated, and dried at 50°C to constant weight to obtain finished fiber.
[0044] Example 6
[0045] In Example 1, during the soaking process of the enzyme solution, pectinase and deionized water were prepared by adding 1 g of pectinase to 5 L of water, and the rest was the same as in Example 1.
[0046] Example 7
[0047] In Example 1, during the soaking process of the enzyme solution, ligninase and deionized water were prepared by adding 1 g of ligninase to 5 L of water, and the rest was the same as in Example 1.
[0048] Example 8
[0049] In Example 1, the crude fiber is obtained by soaking the linen yarn treated with the composite enzyme solution in a urea solution. The urea solution is prepared by mixing urea and deionized water in a mass ratio of 1:3. Other aspects are the same as in Example 1.
[0050] Example 9
[0051] In Example 1, the crude fiber is directly soaked in potassium permanganate solution to prepare semi-finished fiber without being soaked in ammonium bicarbonate solution. Other steps are the same as in Example 1.
[0052] Example 10
[0053] In Example 1, the semi-finished fiber was fully washed with deionized water, dehydrated, and dried at 75° C. in a vacuum environment to a constant weight. The glycerol solution was not used for soaking. Other aspects were the same as in Example 1.
[0054] The finished fibers prepared in Examples 1 to 10 were tested for elongation at break and breaking strength using an XQ-1 electronic single fiber strength tester. The results are shown in Table 1 below.
[0055] Table 1 Test results of mechanical properties of finished fiber
[0056] Breaking strength (cN / tex) Elongation at break (%) Example 1 68.1 3.67 Example 2 65.4 3.69 Example 3 66.9 3.71 Example 4 67.8 3.68 Example 5 66.3 3.75 Example 6 61.1 3.04 Example 7 59.8 3.12 Example 8 60.2 2.93 Example 9 56.7 2.24 Example 10 58.4 2.37
[0057] As shown in Table 1, a specific treatment process will help improve the tensile strength and elongation at break of linen yarn fibers, improve the tensile strength of linen yarn fibers, and realize that after the linen yarn fibers are prepared into linen yarn fiber lines through a spinning process, their breakage rate is greatly reduced, the linen yarn breakage is reduced, and the quality of linen yarn textiles is improved; the invention is treated by soaking in a composite enzyme solution, which helps to reduce surface impurities, so that the linen yarn fibers are exposed, and then soaked in an NH3-urea solution to improve the performance of the linen yarn fibers, for example: improve its swelling performance, ensure that the subsequent use of ammonium bicarbonate solution-potassium permanganate solution-propylene glycol solution to soak the linen yarn in sequence, to achieve a more uniform treatment, and then improve the tensile strength and elongation at break of the linen yarn fibers, and improve the ductility of the linen yarn fibers. It has been determined that the invention can make the tensile strength of the linen yarn fibers reach more than 65.4cN / tex, and the elongation at break reach more than 3.67%.
[0058] Based on Example 1, the researchers conducted a study on the effect of the amount of ethylene glycol added to the propylene glycol solution on the tensile strength and elongation of linen yarn fibers. The results are shown in Table 2.
[0059] Table 2 Effect of ethylene glycol addition on mechanical properties of finished fiber based on process of Example 1
[0060] 0.5% 1% 2% 3% 4% 5% 6% 7% 8% Breaking strength (cN / tex) 68.3 69.7 72.3 73.4 73.9 70.6 70.2 70.9 67.1 Elongation at break (%) 3.66 3.72 3.91 3.89 3.83 3.78 3.84 3.71 3.69
[0061] It can be seen from Tables 1 and 2 that adding an appropriate amount of ethylene glycol to the propylene glycol solution will improve the tensile strength and elongation at break of the linen yarn fiber to a certain extent, but excessive addition will lead to poor performance. Therefore, it is necessary to properly control the amount of ethylene glycol added to ensure the quality of the resulting linen yarn finished fiber.
[0062] In order to better explore the range of ethylene glycol addition that should be controlled more accurately, based on the above research, the researchers conducted further experimental research within the optimal range of 2-4% of ethylene glycol addition. It was found that when ethylene glycol accounts for 2.6%-3.7% of the mass of propylene glycol, the tensile strength of the linen yarn fiber can reach above 76.4cN / tex, and the elongation at break can reach above 3.96%. Especially when the ethylene glycol amount is controlled at 3.2% of the mass of propylene glycol, the tensile strength at break reaches 78.5cN / tex, and the elongation at break reaches 4.13%, which greatly improves the mechanical properties of the linen yarn fiber, and the breakage rate of the linen yarn prepared by spinning the linen yarn fiber using traditional spinning technology can be greatly reduced, which greatly guarantees the quality of the linen yarn.
[0063] Other matters not covered by the present invention may be implemented by referring to the prior art or common knowledge and conventional technical means known to those skilled in the art.
[0064] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing modified flax yarn capable of reducing flax yarn breakage, characterized in that: The following steps are involved: (1) soaking the flax yarn in a composite enzyme solution for 10-15 minutes, then taking it out and drying it in a natural environment to constant weight, then treating it with NH3-urea solution for 5-15 minutes, and then taking it out and drying it to constant weight to obtain crude fiber; (2) soaking the crude product in an ammonium bicarbonate solution for at least 30 minutes, then taking it out and soaking it in a potassium permanganate solution in the dark for 30 minutes, taking it out, washing it thoroughly with deionized water, dehydrating it, and drying it to a constant weight to obtain a semi-finished fiber; (3) soaking the semi-finished product in a propylene glycol solution for 15-20 minutes, then washing it with deionized water, dehydrating it, and drying it to a constant weight to obtain a finished fiber; (4) spinning the finished fiber into flax yarn to obtain; The concentration of the glycerol solution is 3-5 g / L and the temperature is 10-15°C; The glycerol solution is added with ethylene glycol accounting for 1-7% of the mass of glycerol; The ethylene glycol accounts for 2.6-3.7% of the mass of the glycerol.
2. The method for preparing modified flax yarn capable of reducing flax yarn breakage according to claim 1, characterized in that: The composite enzyme solution is a solution formed by mixing pectinase and ligninase in a mass ratio of 1:0.3-1, adding 5-10L of water to 1g of the mixed enzyme, and adjusting the temperature to 60-80°C.
3. The method for preparing modified flax yarn capable of reducing flax yarn breakage according to claim 1, characterized in that: The NH3-urea solution is prepared by mixing urea and deionized water in a mass ratio of 1:3-5 to form a solution, introducing ammonia gas or adding ammonium ion components into the solution, adjusting the ammonium ion content in the solution to 5-10 g / L, and adjusting the temperature to 5-10° C. to obtain a mixed solution.
4. The method for preparing modified flax yarn capable of reducing flax yarn breakage according to claim 1, characterized in that: The ammonium bicarbonate solution immersion is carried out at a constant temperature of 40° C. using an ammonium bicarbonate solution with a concentration of 15-20 g / L.
5. The method for preparing modified flax yarn capable of reducing flax yarn breakage according to claim 1, characterized in that: The concentration of the potassium permanganate solution is 6-10 g / L, and the temperature is 40-50°C.
6. The method for preparing modified flax yarn capable of reducing flax yarn breakage according to claim 1, characterized in that: The ethylene glycol accounts for 3.2% of the mass of the glycerol.
7. The method for preparing modified flax yarn capable of reducing flax yarn breakage according to claim 1, characterized in that: The immersion is carried out by mixing according to a water bath ratio of 1:25-30.
Citation Information
Patent Citations
Treatment method for improving mechanical properties of flax yarns
CN109235047A
Biological enzyme degumming method of flax fiber
CN103397391A
Chemical modification method of short flax fibers
CN106555334A
Method for degumming flax
CN109989114A
Fast curing epoxy resin system for glass fiber pultrusion frame and preparation method of fast curing epoxy resin system
CN114573951A